Open source systems 16th IFIP WG 2. 13 International Conference, OSS 2020, Innopolis, Russia, May 12-14, 2020, Proceedings /: 16th IFIP WG 2. 13 International Conference, OSS 2020, Innopolis, Russia, May 12-14, 2020, Proceedings. (2020) - Unknown
No abstract available